Pengaruh Pendapatan Domestik Bruto, Nilai Kurs, Dan Penanaman Modal Asing Terhadap Utang Luar Negeri Indonesia Periode 1990-2022 - Rahel Veronika; Fitrawaty Fitrawaty; Rona Hinirim; Yohana Feby (BADAN PENERBIT STIEPARI PRESS, 2024)
The purpose of this study was to analyze the effect of Gross Domestic Income, Exchange Rate, and Foreign Investment on foreign debt in Indonesia for the period 1990-2022. This study uses quantitative data. This study uses multiple linear regression statistical tests with the Ordinary Least Square (OLS) approach. From the results of the determination test, it can be seen that the R-squared value of 0.914054 indicates that the X1, X2 and X3 variables (GDP, KURS and FDI) simultaneously influence the Foreign Debt (Y) variable by 91.40%, and the remaining 8.60% is influenced by other variables not included in this study.